Analisis Efektivitas Penerimaan Pajak Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) serta Kontribusinya Sebagai Salah Satu Sumber Pendapatan Asli Daerah (PAD) - Indah Permatasari, Riska; Wafirotin, Khusnatul Zulfa (Jurnal Ilmiah Raflesia Akuntansi, 2023)
The purpose of research is to analyze the effectiveness a taxrevenue of Tax on Acquistion of Land and Building as well as its contribution to thelocal revenue in Ponorogo regency on 2018 – 2022 year. This research is the casestudy in Ponorogo regency goverment on 2018 – 2022 year. This research took asecondary data from BPPKAD Ponorogo regency. Technical analysis of the dataused the analysis of effectiveness and analysis contribution. Theresults of the analysis effectiveness concluded that the tax BPHTB in 2018 – 2022year had an average effective rate of 139%, this shows that a tax revenue BPHTBon 2018 – 2022 year can said to be effective as a percentage of more than onehundred percent effectiveness. The analysis of contribution a tax BPHTB to the localrevenue in Ponorogo regency on 2018 – 2022 year had an average contribution rateof 6,18% this shows that the contribution to the local revenue in Ponorogo regencyon 2018 – 2022 year is said very less because had contribute for less than ten percentagecontribution percent.